2014
DOI: 10.1371/journal.pone.0104479
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Release of IL-1s from Skin Is Associated with Systemic Cardio-Vascular Disease, Emaciation and Systemic Amyloidosis: The Potential of Anti-IL-1 Therapy for Systemic Inflammatory Diseases

Abstract: The skin is an immune organ that contains innate and acquired immune systems and thus is able to respond to exogenous stimuli producing large amount of proinflammatory cytokines including IL-1 and IL-1 family members. The role of the epidermal IL-1 is not limited to initiation of local inflammatory responses, but also to induction of systemic inflammation. However, association of persistent release of IL-1 family members from severe skin inflammatory diseases such as psoriasis, epidermolysis bullosa, atopic de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
71
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(75 citation statements)
references
References 25 publications
4
71
0
Order By: Relevance
“…In chapter 7 we are the first to show that serum IL-1Rα, IL-1β and IL-1R1 levels are significantly different in AD compared to healthy controls. This supports the concept of an inflammatory skin march, 58,59 in which spilled-over IL-1s from inflamed skin end up into the circulation, thereby affecting distant organs and causing cardiovascular changes. Whether serum levels of IL-1s decrease during treatment, and the subsequent effect on cardiovascular risk factors, is unknown and has yet to be studied.…”
Section: Atopic Dermatitis Is a Systemic Diseasesupporting
confidence: 81%
See 1 more Smart Citation
“…In chapter 7 we are the first to show that serum IL-1Rα, IL-1β and IL-1R1 levels are significantly different in AD compared to healthy controls. This supports the concept of an inflammatory skin march, 58,59 in which spilled-over IL-1s from inflamed skin end up into the circulation, thereby affecting distant organs and causing cardiovascular changes. Whether serum levels of IL-1s decrease during treatment, and the subsequent effect on cardiovascular risk factors, is unknown and has yet to be studied.…”
Section: Atopic Dermatitis Is a Systemic Diseasesupporting
confidence: 81%
“…57 The association between adult AD and CVD, would be consistent with a recent study that showed the occurrence of severe CVD and metabolic abnormalities in a mouse model of severe dermatitis resulting from persistent release of IL-1 family cytokines from the skin. 58 Interestingly, these pathologies were ameliorated by combination treatment with anti-IL-1α-and anti-IL-1β neutralizing antibodies. In chapter 7 we are the first to show that serum IL-1Rα, IL-1β and IL-1R1 levels are significantly different in AD compared to healthy controls.…”
Section: Atopic Dermatitis Is a Systemic Diseasementioning
confidence: 99%
“…A very recent study showed an increased occurrence of cardiovascular risk proteins in serum . Finally, one mouse study showed that persistent interleukin (IL)‐1 secretion from the skin was associated with CVD, and in line with this observation, an ‘epidermal IL‐1 march’ was recently described as a potential link between the skin and vascular disease in AD …”
Section: Discussionmentioning
confidence: 82%
“…IFN-γ is considered a prototypic proinflammatory biomarker of autoimmune inflammation, and its administration to mice results in accelerated autoimmune diseases [23]. In experimental animals, persistent release of IL-1 family members has been associated with the occurrence of severe systemic cardiovascular diseases and metabolic abnormalities, including aberrant vascular wall remodeling with aortic stenosis, cardiomegaly, impaired limb, tail circulation, fatty tissue loss and systemic amyloid deposition in multiple organs with liver and kidney dysfunction [24]. Increases in IL-6 could have a relevant effect because this cytokine promotes Th17 differentiation.…”
Section: Discussionmentioning
confidence: 99%